Vitamin D effects on Chlamydia trachomatis infection: a case-control and experimental study - Liu, Sijia; Zhao, Tianwei; Liu, Quanzhong (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction Vitamin D deficiency is the most common nutritional deficiency worldwide. Chronic vitamin D deficiency causes immune system dysfunction, which increases susceptibility to pathogens such as bacteria, especially intracellular parasites, and viruses. Chlamydia trachomatis (C. t) is an obligate intracellular parasitic bacterium that causes a variety of sequelae. We speculated that vitamin D might be associated with C. t infection. This study aimed to address this gap in knowledge by investigating the relationship between vitamin D and C. t infection using both in vitro and in vivo models. Methods and results The addition of calcitriol to McCoy cell culture in vitro delayed and reduced the quantity and volume of inclusions compared to the control group. Macrophages of peritoneally lavaged mice co-cultured with McCoy decreased the infection rate and delayed the appearance of inclusions. In mice models of vitamin D deficiency, mice in the VD-group exhibited more severe genital tract inflammation and a longer duration of infection after inoculation with C. t in the genital tract. Supplementing these mice with vitamin D3 during treatment enhanced the therapeutic effect of antibiotics. We also conducted a case-control study involving 174 C. t-positive patients (95 males and 79 females) and 380 healthy volunteers (211 males and 169 females) aged 20–49 from January 2016 to March 15, 2017. Serum 25-(OH)D concentration was measured by assessing morning fasting blood samples of healthy volunteers and C. t-positive patients 1 day before antibiotic treatment and the next day after one course of treatment. The patients were followed up for 1 month and evaluated for recovery. The results showed that vitamin D deficiency was a risk factor for C. t infection and treatment failure. Conclusion In summary, findings from experimental and clinical studies indicate a close association between vitamin D levels and C. t infection and treatment outcomes. Given the affordability and safety of vitamin D, both healthy individuals and patients should focus on vitamin D intake. Vitamin D supplementation could enhance treatment success and should be used as an adjunctive therapy alongside antibiotic therapy for C. t infections, pending confirmation in larger, prospective, randomized controlled trials.